2001
DOI: 10.1046/j.1365-2567.2001.01214.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium avium infection in CD14‐deficient mice fails to substantiate a significant role for CD14 in antimycobacterial protection or granulomatous inflammation

Abstract: SUMMARYCD14 is a pattern-recognition receptor implicated in the in¯ammatory response to microbial components such as lipopolysaccharide, peptidoglycan and lipoarabinomannan. In this work, we made use of CD14-de®cient (CD14x/x) mice to evaluate the relative importance of CD14 in response to infection with viable, intact cells of Mycobacterium avium in vitro and in vivo. Following co-incubation of either bone marrow-derived macrophages (Mw) or thioglycollate-elicited peritoneal Mw from CD14x/x mice with viable M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…In contrast, TNF-␣ secretion by M exposed to purified cell walls or peptidoglycan demonstrated a clear reliance on CD14. Similarly, CD14 deficiency does not alter granuloma formation, TNF-␣ and IFN-␥ mRNA levels, or bacterial burdens associated with mycobacterial infection (68). Only thioglycolateelicited peritoneal M from the two genotypes exhibited CD14-dependent differences in TNF-␣ and IL-6 secretion.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In contrast, TNF-␣ secretion by M exposed to purified cell walls or peptidoglycan demonstrated a clear reliance on CD14. Similarly, CD14 deficiency does not alter granuloma formation, TNF-␣ and IFN-␥ mRNA levels, or bacterial burdens associated with mycobacterial infection (68). Only thioglycolateelicited peritoneal M from the two genotypes exhibited CD14-dependent differences in TNF-␣ and IL-6 secretion.…”
Section: Discussionmentioning
confidence: 87%
“…For example, treatment of rabbits with anti-CD14 mAb exacerbates tissue injury and undermines control of bacterial growth in models of Shigella flexneri (61) and E. coli infection (62). The picture in mice is more complex, with the role of CD14 depending upon inoculum size and whether intact organisms or purified PAMPs are used (40,(63)(64)(65)(66). CD14 KO mice challenged with either E. coli 0111 or its LPS or with Salmonella typhimurium are resistant to their lethal effects and produce very low amounts of proinflammatory cytokines compared with their WT counterparts (40,67).…”
Section: Discussionmentioning
confidence: 99%
“…RT-PCR was performed essentially as described previously (33). In brief, weighed lung tissue samples were homogenized in 5 ml of 4 M guanidinium-isothiocynanate buffer and diluted to obtain equalized amounts of milligrams of lung per milliliter of buffer.…”
Section: Rt-pcrmentioning
confidence: 99%
“…21 Of note, Ehlers et al reported similar bacterial loads in lungs, liver and spleen of CD14 KO and WT mice during an 8-week follow up after intravenous infection with M. avium. 16 It appears striking that several studies investigating the role of TLRs and TLR associated molecules in mycobacterial infection are divergent in their results. 15,17,[33][34][35][36][37][38][39][40][41][42][43] The results of these studies differ from none, moderate or even strong effects because of the lack of a TLR or TLR associated molecule.…”
Section: Discussionmentioning
confidence: 99%
“…15 In addition, although the absence of CD14 resulted in a reduced and delayed release of tumour necrosis factor-a (TNF) by macrophages infected with M. avium in vitro, CD14 knockout (KO) mice displayed an unaltered antibacterial defence and granulomatous reaction after intravenous infection with M. avium in vivo. 16 Thus far, only one study examined the contribution of CD14 to host defence against lung tuberculosis reporting that CD14 KO mice had an immune response that was indistinguishable from that in normal wild-type (WT) mice during a 14-week follow up after aerosol M. tuberculosis infection. 17 We here report CD14 KO mice are protected from mortality from lung tuberculosis occurring in WT mice from 20 weeks after infection, which is accompanied by reduced lung inflammation.…”
Section: Introductionmentioning
confidence: 99%